(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To determine the prevalence of sleep disorders and associated factors in elderly people with type 2 diabetes. Methods: This descriptive cross-sectional study included 248 elderly patients with type 2 diabetes at the Thu Duc City Hospital clinic. Patients were interviewed using a questionnaire that covered their current medical conditions and assessed sleep disorders using the Pittsburgh Sleep Quality Index (PSQI). Results: The prevalence of sleep disorders among elderly patients with type 2 diabetes was 75.4%. Factors such as being female, living outside Ho Chi Minh City, longer duration of diabetes, use of multiple medications, and being overweight or obese were associated with a higher rate of sleep disorders. Conclusion: Elderly individuals with type 2 diabetes are at a high risk of sleep disorders, emphasizing the need for healthcare providers to pay closer attention to this issue and provide additional support to affected patients.